Ćwiczenie 3
Oblicz wartość wyrażenia dla podanych wartości zmiennych.
a) y(2x – 3y)-(y2 - xy) – 2y2 dla x = -0,3 i y=1 2
-
3 ​


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

a)

y(2x – 3y)-(y2 - xy) – 2y2 dla x = -0,3 i y=1 2   to  

y(2x – 3y)-(y² - xy) – 2y² dla x = - 0,3 i y = ½ =

= ½(-0,3•2 - 3/2) - (1/4 - (-0,3)•(1/2)) - 2•(1/4) =

= ½(-(3/10)•2 - 3/2) - (1/4 + (3/10)•(1/2)) - 2/4 =

= ½(- 6/10 - 15/10) - (1/4 +3/20) - 10/20 =

= - 6/20 - 15/20 - 5/20 - 3/20 - 10/20 =

= - (6 + 15 + 5 + 3 + 10)/20 = - 39/20 = - 20/20 - 19/20 =

= - 1 - 19/20 = - 1i19/20 ( minus 1 cała i 1/20)